(untitled) (TAMADDUN NURI JURNALI, 2024)
The article describes the activities of religious figures in our country in the 20th century, their relationship with the authorities, as well as the difficult religious situation during the period of tsarist Russia and the Soviet Union. The author analyzes the events associated with the creation of the religious administration of Muslims of Central Asia and Kazakhstan, the period of the muftis of the Babakhan dynasty and draws the appropriate conclusions.